The Use of Gondok Cigarette Into Brickets as Fuel Products in Replacement of Alternative Energy Sources at Soko Glagah District - Safitri, Dian; Safitri, Kiki Irnanda; Syaifullah, Agung Debby Achmad; Rohman, Roy Abdul; Rizqi, Moh. (Kontribusia : Research Dissemination for Community Development, 2018)
Geographically, Soko Village is in Glagah District of Lamongan Regency. Regency of Morocalan in the north, Gempol Pendowo in the east, Punan Village in the south, Blawi Village in the west. In general, the livelihoods of Soko villagers are identified in several sectors, fishers, traders, civil servants, employees and others. Most of the work of the residents is fish seed entrepreneurs. One of the factors that influence fish growth is irrigation. Watering is one of the things that affect the growth of fish, but the ponds in the village of Soko filled with water hyacinth that can inhibit the growth of fish. If this is not addressed, then it will have a fatal impact on the growth of the fish itself. The results of the work program held by the Industrial Engineering program group 4 by executing the manufacture of water hyacinth briquettes can help reduce the water hyacinth waste in the pond. Moreover, also the village government should be able to conduct an in-depth review to provide progress and mutual benefit for both the community and government.